A two-part phase I study to establish and compare the safety and local tolerability of two nasal formulations of XF-73 for decolonization of Staphylococcus aureus: A previously investigated 0.5 mg/g viscosified gel formulation versus a modified formulation - Yendewa, George A. (J Glob Antimicrob Resist, 2019)
OBJECTIVES: There is conflicting data on the success of mupirocin as an effective decolonizing regimen for Staphylococcus aureus (SA) carriage, in part due to increasing drug resistance. This multi-center, randomized, open-label, prospective phase 1 study compared the safety and local tolerability of two nasal formulations of XF-73, a novel porphyrinic antibacterial drug with rapid intrinsic activity against SA. METHODS: The study was conducted in 2 dosing cohorts, and enrolled 60 healthy adults. In Part 1, 8 non-SA carriers were randomized to 2 groups of 4 subjects in each arm and were treated with the new formulations of XF-73 in concentrations of 0.5 mg/g 2% gel and 2 mg/g 2% gel, respectively. In Part 2, 52 healthy persistent SA carriers were randomized to 4 groups of 13 subjects in each arm and were treated with three different concentrations of XF-73 (0.5 mg/g 2% gel, 2 mg/g 2% gel and 0.5 mg/g 4% gel) or a 4% viscosified placebo gel, respectively. Plasma pharmacokinetics (PK) and pharmacodynamics (PD) studies were performed. Anti-staphylococcal activity was assessed as the presence or absence of SA and by quantification of the level of colonization using a semi-quantitative scale (SA score). RESULTS: 56 subjects (8/8 from Part 1 and 48/52 from Part 2) completed the study, with 47/60 comprising the PK population and 48/60 the PD population. There was no measurable systemic absorption of XF-73 from nasal application. Treatment with XF-73 was associated with a rapid diminution in the SA scores in all subjects. The most common treatment emergent adverse events (TEAE) reported were rhinorrhea and nasal dryness (15.5% each in Part 1 and Part 2). TEAEs were mostly mild and resolved spontaneously. CONCLUSION: XF-73 was found to be safe and was tolerated with minimal side effects at doses of 0.5mg/g 2% gel and 2mg/g 2% gel in healthy volunteers. These findings support moving on to Phase 2 trials to further evaluate the efficacy of XF-73.